Talent management: a Delphi study of assessing and developing GenZ hospitality leaders. Issue 10 (14th October 2019) - Self, Timothy T.; Gordon, Susan; Jolly, Phillip M.
Abstract : Purpose: This study aims to examine how hospitality human resource (HR) professionals assess talent when recruiting college students, how MIT programs are structured and how recruiters perceive GenZ compared to Millennials. Design/methodology/approach: A Delphi approach was used to collect the opinions of experts in the area of hospitality recruiting and talent development. Findings: Results showed integrity and strong work ethic are top descriptors to define talent, and prior performance and soft skills are top items assessed when hiring talent. The participants view GenZ as desiring work-life balance, tech savvy, interested in social responsibility, more accepting of differences, wanting higher salaries and more tech savvy than Millennials. Practical implications: Recruiters highly value prior work experience so students should be encouraged to pursue internships with companies they are interested in working for upon graduation. Providing mock interviews and networking events can help students better their soft skills. Organizations using MIT programs should use realistic job previews in the selection process and make regular coaching and mentoring a key part of the program. Hospitality organizations should place emphasis on GenZ's quest for work-life balance and find ways to take advantage of their technology savviness. Originality/value: This study is one of the first to understand how hospitality organizations' MIT programs are structured. It is one of the few to examine how talent is defined and assessed by hospitality HR professionals and compare HR professionals' perceptions of GenZ versus Millennials.